RETRACTED: Metformin-Enhanced Cardiac AMP-Activated Protein Kinase/Atrogin-1 Pathways Inhibit Charged Multivesicular Body Protein 2B Accumulation in Ischemia–Reperfusion Injury - Li, Tian; Yin, Yue; Mu, Nan; Wang, Yishi; Liu, Manling; Chen, Mai; Jiang, Wenhua; Yu, Lu; Li, Yan; Ma, Heng (Frontiers in Cell and Developmental Biology, 2021)
Background: Cardiac autophagic flux is impaired during myocardial ischemia/reperfusion (MI/R). Impaired autophagic flux may exacerbate MI/R injury. Charged multivesicular body protein 2B (CHMP2B) is a subunit of the endosomal sorting complex required for transport (ESCRT-III) complex that is required for autophagy. However, the reverse role of CHMP2B accumulation in autophagy and MI/R injury has not been established. The objective of this article is to elucidate the roles of AMPK/Atrogin-1 pathways in inhibiting CHMP2B accumulation in ischemia–reperfusion injury. Methods: Male C57BL/6 mice (3 months) and H9c2 cardiomyocytes were used to evaluate I/R and hypoxia/reoxygenation (H/R) injury in vivo and in vitro, respectively. I/R was built by a left lateral thoracotomy and occluded left anterior descending artery. H9c2 cells were firstly treated in 95% N2 and 5% CO2 for 15 h and reoxygenation for 1 h. Metformin (100 mg/kg/d) and CHMP2B (Ad-CHMP2B) transfected adenoviruses were administered to the mice. The H9c2 cells were treated with metformin (2.5 mM), MG-132 (10 μM), bafilomycin A1 (10 nM), and Compound C (20 μM). Results: Autophagic flux was found to be inhibited in H/R-treated cardiomyocytes and I/R mice, with elevated cardiac CHMP2B accumulation. Upregulated CHMP2B levels in the in vivo and in vitro experiments was shown to inhibit autophagic flux leading to the deterioration of H/R-cardiomyocytes and MI/R injury. This finding implies that CHMP2B accumulation increases the risk for myocardial ischemia. Metformin suppressed CHMP2B accumulation and ameliorated H/R-induced autophagic dysfunction by activating AMPK. Activated AMPK up-regulated the mRNA expression and protein levels of Atrogin-1, a muscle-specific ubiquitin-ligase, in the myocardium. Atrogin-1 significantly enhanced the interaction between Atrogin-1 and CHMP2B, therefore, promoting CHMP2B degradation in the I/R myocardium. Finally, this study revealed that Metformin inhibited CHMP2B accumulation induced autophagic impairment and ischemic susceptibility in vivo through the AMPK–regulated CHMP2B degradation by Atrogin-1. Conclusion: Impaired CHMP2B clearance in vitro and in vivo inhibits autophagic flux and weakens the myocardial ischemic tolerance. Metformin treatment degrades CHMP2B through the AMPK-Atrogin-1 dependent pathway to maintain the homeostasis of autophagic flux. This is a novel mechanism that enriches the understanding of cardioprotection.